2011
DOI: 10.1097/fbp.0b013e328347546d
|View full text |Cite
|
Sign up to set email alerts
|

α4β2 nicotinic acetylcholine receptor partial agonists with low intrinsic efficacy have antidepressant-like properties

Abstract: Previous studies have suggested that treatment with antagonists or partial agonists of nicotinic acetylcholine receptors containing the β2 subunit (β2* nAChRs) results in antidepressant-like effects. In the current study we tested 3 novel compounds with different affinity and functional efficacy at α4β2* nAChRs, which were synthesized as part of nAChR discovery projects at Pfizer in the tail suspension, forced swim and novelty-suppressed feeding tests of antidepressant efficacy. All compounds tested reduced im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 41 publications
(74 reference statements)
1
32
1
Order By: Relevance
“…Previous studies show that both sazetidine-A and varenicline ameliorate cognitive withdrawal symptoms (Raybuck et al, 2008;Rezvani et al, 2011) and reduce nicotine self-administration (Levin et al, 2010;O'Connor et al, 2010;Rezvani et al, 2010). Furthermore, both varenicline and sazetidine-A have shown antidepressant efficacy in the forced swim test (Caldarone et al, 2011;Kozikowski et al, 2009;Mineur et al, 2011;Rollema et al, 2009;Turner et al, 2010). In contrast, in conflict anxiety paradigms like the NIH test, we have previously shown that chronic sazetidine-A has anxiolytic effects, while varenicline does not (Turner et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies show that both sazetidine-A and varenicline ameliorate cognitive withdrawal symptoms (Raybuck et al, 2008;Rezvani et al, 2011) and reduce nicotine self-administration (Levin et al, 2010;O'Connor et al, 2010;Rezvani et al, 2010). Furthermore, both varenicline and sazetidine-A have shown antidepressant efficacy in the forced swim test (Caldarone et al, 2011;Kozikowski et al, 2009;Mineur et al, 2011;Rollema et al, 2009;Turner et al, 2010). In contrast, in conflict anxiety paradigms like the NIH test, we have previously shown that chronic sazetidine-A has anxiolytic effects, while varenicline does not (Turner et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…Mice were placed in clear glass beakers (18 cm in diameter) filled with 15 cm water (∼25°C). Videotapes were scored for time spent immobile over a 15-min period as described previously (42). Immobility was defined as the minimal amount of movement made by the mouse to stay afloat.…”
Section: Methodsmentioning
confidence: 99%
“…This could explain why nicotinic signaling has seemingly paradoxical effects: low dose chronic nicotine has a comparable effect to an antagonist of high affinity β2 subunit-containing (β2*) nAChRs in a conditioned emotional response task in mice (Anderson and Brunzell, 2012), and both nicotine and the nicotinic antagonist mecamylamine can increase serotonin release in the hippocampus (Kenny et al, 2000). Several pharmacological studies have confirmed that nicotinic blockers (antagonists or partial agonists) can alleviate depression-like behaviors in mice, either alone or in combination with monoaminergic drugs (Andreasen et al, 2009; Bacher et al, 2009; Mineur et al, 2009; Mineur et al, 2011; Rollema et al, 2009). Interestingly, commonly used antidepressants can also act as α4β2* nAChR antagonists in cell-based assays (Shytle et al, 2002; Slemmer et al, 2000), suggesting that these medications might also act in synergy with nAChR signaling to be fully effective.…”
Section: Introductionmentioning
confidence: 99%